Effects of aging/freezing sequence and freezing rate on meat quality and oxidative stability of pork loins. (May 2018) - Kim, Hyun-Wook; Kim, Ji-Han; Seo, Jin-Kyu; Setyabrata, Derico; Kim, Yuan H. Brad
Abstract: The aim of this study was to evaluate the effect of aging/freezing sequence and freezing rate on quality attributes and oxidative stability of frozen/thawed pork loins ( M. longissimus lumborum, n = 6). Six treatments were prepared by combining 3 aging/freezing sequences (FT, freezing/thawing only; AFT, aging prior to freezing/thawing; and FTA, freezing/thawing and aging) with 2 freezing rates (slow- and fast-freezing). The lowest purge/thaw loss and drip loss were found for AFT, in which fast-freezing reduced total exudate loss ( P < 0.05). Aging combination (AFT/FTA) decreased shear force of frozen/thawed pork loins, and FTA with slow-freezing caused the lowest shear force ( P < 0.05). However, aging combination regardless of the sequence accelerated discoloration and lipid/protein oxidation during display ( P < 0.05). This study suggests that aging prior to freezing coupled with fast-freezing could be an effective way to minimize quality defects of frozen/thawed only meat, particularly water-holding capacity and tenderness. Highlights: Pork loins were assigned to 3 aging/freezing sequences and 2 freezing rates. Aging prior to freezing decreased purge/thaw loss and drip loss. Fast-freezing reduced total exudate loss of aged/frozen/thawed pork loins. The lowest shear force resulted from slow freezing first then thaw/aging. Aging then fast-freezing/thawing could be the most effective method.